Morroniside induces cardiomyocyte cell cycle activity and promotes cardiac repair after myocardial infarction in adult rats - Zheng, Songyang; Liu, Tingting; Chen, Mengqi; Sun, Fangling; Fei, Yihuan; Chen, Yanxi; Tian, Xin; Wu, Zheng; Zhu, Zixin; Zheng, Wenrong; Wang, Yufeng; Wang, Wen (Frontiers in Pharmacology, 2024)
Acute myocardial infarction (AMI) is characterized by the loss of cardiomyocytes, which impairs cardiac function and eventually leads to heart failure. The induction of cardiomyocyte cell cycle activity provides a new treatment strategy for the repair of heart damage. Our previous study demonstrated that morroniside exerts cardioprotective effects. This study investigated the effects and underlying mechanisms of action of morroniside on cardiomyocyte cell cycle activity and cardiac repair following AMI. Neonatal rat cardiomyocytes (NRCMs) were isolated and exposed to oxygen-glucose deprivation (OGD) in vitro. A rat model of AMI was established by ligation of the left anterior descending coronary artery (LAD) in vivo. Immunofluorescence staining was performed to detect newly generated cardiomyocytes. Western blotting was performed to assess the expression of cell cycle-related proteins. Electrocardiography (ECG) was used to examine pathological Q waves. Masson's trichrome and wheat germ agglutinin (WGA) staining assessed myocardial fibrosis and hypertrophy. The results showed that morroniside induced cardiomyocyte cell cycle activity and increased the levels of cell cycle proteins, including cyclin D1, CDK4, cyclin A2, and cyclin B1, both in vitro and in vivo. Moreover, morroniside reduced myocardial fibrosis and remodeling. In conclusion, our study demonstrated that morroniside stimulates cardiomyocyte cell cycle activity and cardiac repair in adult rats, and that these effects may be related to the upregulation of cell cycle proteins.